Kepemimpinan, kompensasi, dan kinerja marketer pada PT. Shinari Putra Kencana Kabupaten Bandung - Mulyana, Iwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Human resources (HR) play an important role, especially in the lives of public organizations, because they are the main determinant of improving organizational performance, and their role cannot be replaced by anything. The research aims to find out how leadership and compensation influence the performance of marketers at PT. Shinari Putra Kencana. The method used in this research is a quantitative descriptive method. The research sample used a questionnaire and made the population the research sample. The sample in this study was 12 respondents from marketers at PT. Shinari Putra Kencana. Based on the results of the hypothesis analysis, leadership and performance have a significant effect on employee performance, and leaders always show appreciation for improving employee performance. The findings in this study reveal that the better the leadership and the better the compensation given, the more performance will increase.